Electricity Accounts Receivables Billing Procedures - Arif Darmawan; Stevani Patrecia Bangun (Pusat P2M Politeknik Negeri Batam, 2016)
The purpose of this research is to know how electricity accounts receivable billing procedures. This research was conducted at PT PLN Batam, liquid service companies. This method is used in such research is a descriptive analysis method. The results of this research it can be concluded that the services are used by customers each month will be paid in the following month, thus the company has accounts receivable. In accordance with the statutes, PT PLN, the arrears account customers of electricity will be subject to fines or late payment fees. The fines shall be paid in accordance with the statutes, parties PLN gradually starting from the first sheet second sheet, fines, and a third sheet. To make a payment to a fine sheet of resources and must comply with the tariffs, also performed the first sheet while in the disconnection, update the data in the sheet. Payments are made based on the recording meter. The occurrence of error logging meters due to the kWh meters high, kWh meter, kWh meter building in the blurry due to factors of sanggarnya kWh, and the address is not found because it was moved by irresponsible persons. The error will cause losses to customers and the repair will be performed if an error occurred.